The Effectiveness of the Problem Based Learning Model on Elementary School Students' Mathematics Learning Outcomes - Muliawati, Ida; Aldin, Ahadiyah (Journal of Indonesian Primary School, 2024)
This research aims to improve student learning outcomes in mathematics learning by implementing a problem-based learning model. This research is experimental research. The research design used is one group design. The sample for this research was class VI MIN 3 West Aceh students. The data in this research was collected using observation and test techniques. The data obtained was then analyzed using descriptive statistical techniques and t-test. The results of the research show that the problem-based learning model has a significant impact on student learning outcomes in class VI mathematics at SD Islam Negeri 3 Aceh Barat. This is proven by the t-test results which show that the significance value is <0.005, which means there is a difference between before and after treatment. Based on these results, it can be concluded that the problem-based learning model can be used as a model that can overcome the problem of low student mathematics learning outcomes at elementary school level.